1998
DOI: 10.1023/a:1022302228051
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have studied the expression of the lipopolysaccharide (LPS) receptor CD14 on monocytes (Mo) and alveolar macrophages (AM), including density- and size-defined subpopulations. Bronchoalveolar lavage (BAL) was performed on eleven healthy non-smokers and blood sampled from 5 of them, and the levels of cell CD14 expression was investigated using flow cytometry. The influence of LPS stimulation on the CD14 expression of AM was studied at various intervals during prolonged incubation. Further, the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…We were able to show that CD14 is marginally expressed in human AM as well as IM. Low CD14 expression was reported previously for human AM obtained from bronchoalveolar lavage [28,29]. CD14 expression by human IM is not described in the literature, but our results resemble findings reported for other tissue macrophage populations [28].…”
Section: Discussionsupporting
confidence: 88%
“…We were able to show that CD14 is marginally expressed in human AM as well as IM. Low CD14 expression was reported previously for human AM obtained from bronchoalveolar lavage [28,29]. CD14 expression by human IM is not described in the literature, but our results resemble findings reported for other tissue macrophage populations [28].…”
Section: Discussionsupporting
confidence: 88%
“…Scientific evidence shows CD14 is vital for TLR4 signalling via the MyD88independent pathway [38]. As the results described in this paper confirm, CD14 gene expression is increased by LPS in alveolar macrophages after several hours of infection [39], TLR4 gene expression is decreased by LPS infection of mouse macrophages [40], and MD2 gene expression is higher after LPS infection of alveolar macrophages [41]. Furthermore, our data show, in Figures 3 and 4, that LPCAT2 regulated these molecules' gene expression, albeit only in non-infected and E. coli O111:B4-infected macrophages.…”
Section: Discussionsupporting
confidence: 81%
“…Alexis et al demonstrated that neutrophil elastase reduced CD14 expression on alveolar phagocytes in vitro , which might represent the underlying cause for the low mCD14 expression on CF alveolar macrophages [32,33]. Two previous studies demonstrated that short-term incubation with LPS decreased mCD14, whereas long-term LPS treatment resulted in increased mCD14 expression on monocytes [21] and alveolar macrophages [34]. Our findings indicate that 40 h incubation with LPS and CpG induced sCD14 secretion and increased mCD14 expression of PBMCs.…”
Section: Discussionmentioning
confidence: 99%